The economic impact of disease-related malnutrition at hospital admission - Teresa F Amaral (2007)
Background & aims: The reported frequency of disease-related malnutrition (DRM) for patients admitted to hospitals has been shown to be high, but an accurate estimate of the magnitude of its economic costs is lacking. The objective of this study was to determine the impact of DRM on hospitalization costs. Methods: A probabilistic sample of 469 (50%) patients from two hospitals was recruited on a cross-sectional study. DRM was evaluated by the Nutritional Risk Screening-2002 instrument at hospital admission and hospitalization costs were calculated for each patient based on hospital length of stay and on the discharge diagnosis-related group (DRG) code. Estimates of the association between DRM and deviations from the mean cost within each DRG were carried out. Results: Patients classified as nutritionally-at-risk accounted for 42% of the sample. Multivariate estimates of the determinants of cost deviation shows that the cost of treating a nutritionally-at-risk patient is 20% higher than the average of the respective DRG. Patients that are classified on DRG classes that have a higher relative weight are less likely to end up with hospitalization costs above the mean. Conclusions: Considering this sample case-mix, DRM can represent an increase in costs of 19.3%, or between 200 and 1500(sic), with a confidence of 95%.